The effects of non-surgical periodontal therapy (NSPT) on periodontal parameters, levels of inflammatory markers and kidney function indicators in chronic kidney disease patients with chronic periodontitis - Chaudhry, Ahmed (2019)
Chronic kidney disease (CKD) is associated with periodontal disease due to the hyperinflammatory state in both conditions. Hence periodontal disease has emerged as a non-traditional risk factor for CKD. Non-surgical periodontal therapy (NSPT) is a standard treatment for periodontitis. However, limited is known about the effect of NSPT on periodontal parameters in pre-dialysis CKD patients with chronic periodontitis (CP) in our local population. This study was aimed to investigate and compare the effects of non-surgical periodontal therapy (NSPT) on clinical periodontal parameters and the levels of inflammatory markers (hs-CRP, IL-6) in CKD patients with CP and CP only patients. Moreover, the aim was to determine the effects of NSPT on kidney function indicators in CKD and CP patients. A total of 66 patients which consisted of 33 chronic periodontitis patient with no medical illness (Group 1) and 33 pre-dialysis CKD stage III and IV patients with chronic periodontitis (Group 2) were enrolled. Clinical periodontal parameters including periodontal pocket depth (PPD), clinical attachment loss (CAL), gingival bleeding index (GBI) and plaque score (PS) were evaluated during the first visit and six weeks following NSPT (second visit). Blood samples were also obtained during both visits for the analysis of hs-CRP, IL-6, serum urea and serum creatinine (for estimation of GFR).CKD patients with chronic periodontitis (group 2) had shown significantly higher (p<0.05) levels of clinical periodontal parameters at baseline as compared to the patients with chronic periodontitis only (group 1). Inflammatory markers (hs-CRP and IL-6) levels were also found significantly higher (p<0.05) in group 2 as compared to group 1 patients. Significant reduction (p<0.05) was recorded in all the clinical periodontal parameters and inflammatory markers in both groups following NSPT. However, the mean difference of 0.27 for serum urea levels and 0.21 for eGFR showed mild improvement of kidney function in group 2 patients following NSPT. The clinical periodontal parameters and levels of inflammatory markers improved in both the groups following NSPT. Although kidney function indicators showed no significant difference following NSPT, there was a slight improvement. Thus NSPT may play a role be helpful in halting the progression of CKD Therefore, the periodontal health of CKD patients’ needs to be monitored and screened for early dental interventions.